"Her need was greater than my ethical dilemmas": Pastoral, Theological Education. (25th February 2015) - Foskett, John; McConville, Declan
Abstract : Pastoral supervision is growing in importance as an essential part of the ministry of pastoral care and counselling. Pastors, lay and clerical, learn the art and science of care and counselling as much through their experience of ministry as through formal education. The verbatims of conversations and events in ministry area fertile resource for learning both for the individuals, who produce the verbatim, and for those in the supervision group learning from one another. The following verbatim is an example of one chaplain's work and of the dilemmas and demands placed upon him. The record of the interview is enlarged by the supervisee's own reflections and the reactions and comments of the group who role played the verbatim.